1998
DOI: 10.1074/jbc.273.15.9323
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-activated Protein Kinase Phosphatase-3 N-terminal Noncatalytic Region Is Responsible for Tight Substrate Binding and Enzymatic Specificity

Abstract: We have reported recently that the dual specificity mitogen-activated protein kinase phosphatase-3 (MKP-3) elicits highly selective inactivation of the extracellular signal-regulated kinase (ERK) class of mitogen-activated protein (MAP) kinases (Muda, M., Theodosiou, A., Rodrigues, N., Boschert, U., Camps, M., Gillieron, C., Davies, K., Ashworth, A., and Arkinstall, S. (1996) J. Biol. Chem. 271, 27205-27208). We now show that MKP-3 enzymatic specificity is paralleled by tight binding to both ERK1 and ERK2 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
123
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 51 publications
3
123
0
Order By: Relevance
“…The association of ERK1/2 with the dual-specificity phosphatase MKP-3/Pyst1/rVH6 has been recently reported (22,55), and such an association was found to cause catalytic activation of this phosphatase, indicating a model of phosphatase catalytic regulation by substrate binding (56); however, we have not detected changes in the in vitro tyrosine phosphatase activity of PTP-SL for pNPP upon binding to purified recombinant FIG. 7.…”
mentioning
confidence: 44%
“…The association of ERK1/2 with the dual-specificity phosphatase MKP-3/Pyst1/rVH6 has been recently reported (22,55), and such an association was found to cause catalytic activation of this phosphatase, indicating a model of phosphatase catalytic regulation by substrate binding (56); however, we have not detected changes in the in vitro tyrosine phosphatase activity of PTP-SL for pNPP upon binding to purified recombinant FIG. 7.…”
mentioning
confidence: 44%
“…The N-terminal non-catalytic region of DSPs has been shown to be responsible for binding to MAPKs (40). Most mammalian DSPs possess two motifs designated CH2 (Cdc25 homology regions) at the N-terminal half of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobs et al (1999) demonstrated that FXFP is an evolutionarily conserved motif that mediates binding of p42 MAPK to various substrate proteins. The discovery that both substrate specificity and tight substrate binding are conferred by the amino terminus of the related phosphatase MKP-3 (Camps et al, 1998;Muda et al, 1998) supports the hypothesis that the FNFP motif within XCL100 mediates its role as a p42 MAPK substrate. In addition, the absence of an analogous experimentally defined JNK docking site (Yang et al, 1998a,b;Jacobs et al, 1999) in XCL100 is consistent with our conclusion that this phosphatase is a poor substrate for JNK.…”
mentioning
confidence: 88%